G-Protein Coupled Receptors - Saengsawang W. (2023)
G protein coupled receptors (GPCRs) are known to be key regulators for complex biological processes including cell growth, differentiation, motility and death. Therefore, they play crucial roles in the regulation of numerous physiological functions. This article assigns potential interface between GPCR and other signaling pathways including growth factors and microtubule networks. Activation of certain G protein coupled receptors initiates extension of microtubule-based cellular outgrowth, which is due, at least in part, to internalization of the G protein, Gsα, which associates with microtubule plus ends and activates GTPase, increasing dynamic instability of microtubules and promoting neurite outgrowth. The article also introduces GPCRs and G proteins as tools and targets for drug discovery and development and also biomarkers for diseases.